2016
DOI: 10.1177/0887403416640585
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Therapeutic and Militaristic Contexts in a Veteran Treatment Court

Abstract: Recently, the number of veteran treatment courts (VTCs) has greatly expanded. These courts, based on drug treatment court processes, attempt to handle the underlying causes of criminal conduct as well as the instant offense. There is, however, no research that addresses how the military manifests in VTC. We suggest that participants import military culture into VTC processes and that the military will have an influence on VTC proceedings. The purpose of this study is to examine how military and specialty court… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…However, despite the apparent success, the authors argued that challenges remained such as communication, buy-in, protocols, education/training, transportation, scheduling, and discharge upgrades (to qualify for veteran affairs [VA] services and benefits). In addition, this study like many others pointed to the vital role of military culture and peer mentor in creating a trusting and nurturing environment for JIVs (Cartwright, 2011; Douds & Ahlin, 2019; Slattery et al, 2013; Vaughan et al, 2019). Still, this study offered little empirical support for this recommendation.…”
Section: Literature Reviewsupporting
confidence: 61%
See 1 more Smart Citation
“…However, despite the apparent success, the authors argued that challenges remained such as communication, buy-in, protocols, education/training, transportation, scheduling, and discharge upgrades (to qualify for veteran affairs [VA] services and benefits). In addition, this study like many others pointed to the vital role of military culture and peer mentor in creating a trusting and nurturing environment for JIVs (Cartwright, 2011; Douds & Ahlin, 2019; Slattery et al, 2013; Vaughan et al, 2019). Still, this study offered little empirical support for this recommendation.…”
Section: Literature Reviewsupporting
confidence: 61%
“…However, past experiences are contextually important to both VTC participants and VTC team members as they can offer many lessons and shape future behavior (Frederick, 2014). Although VTCs are the newest addition to the specialty courts family in the United States, thus, only providing limited accessible data, some studies have already reported signs of success, although loosely defined and inconsistently measured, from VTC programs (Erickson, 2016; Hartley & Baldwin, 2019; Holbrook & Anderson, 2011; Shannon et al, 2017; Slattery et al, 2013; Vaughan, Holleran, & Brooks, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, other case studies find similar dynamics with regard to how these courts mobilize veteran identity to encourage compliance (see Ahlin and Douds ; Vaughan, Holleran, and Brooks ). However, the challenges that veterans encounter when trying to access health care, partly attributable to the “identity conflict” of being both a soldier and someone in need, mean that VTC graduates may face distinct challenges when it comes to both compliance with the court and continuing medical treatment if and when they are no longer in the court (Smith and True ).…”
Section: Conclusion: Vtcs and Ongoing Criminal Justice Reformmentioning
confidence: 72%
“…Although they have not drawn connections to the SIT tradition, qualitative research has started to identify similar connections between group identification and engagement within VTCs. Specifically, internal association with veteran status as well as camaraderie with other veterans has been shown to influence the decision to enter VTCs (Ahlin & Douds, 2016), motivation to complete the program (Clifford et al, 2014), response to staff (Vaughan et al, 2019), and perceptions of mutual accountability with peers (Baldwin & Rukus, 2015).…”
Section: Social Identity Theory and Veteran Identitymentioning
confidence: 99%